Comparison of outcomes between intra-articular tranexamic acid versus intravenous tranexamic acid in unilateral knee joint replacement - Naqshaband, Mumraiz; Taqi, Muhammd; Ashraf, Sohail; Masood, Faisal; Akhtar, Muhammad; Nadeem, Muhammad Jazib; Raza, Javaid Hassan; Nadeem, Rana Dilawaz (Journal of Fatima Jinnah Medical University, 2021)
Background: The goal of this research was to assess the effectiveness and safety of intra-articular tranexamic acid (TA) with intravenous (IV) TA in reducing perioperative blood loss, the severity of early postoperative problems, and venous thromboembolism in patients who have had a primary unilateral cemented total knee replacement. Patients and methods: This comparative study was undertaken using a non-probability purposive sampling technique at the Department of Orthopedic Surgery, King Edward Medical University / Mayo Hospital, Lahore, from July 1st, 2018 to October 30th, 2019. A total of number 71 patients, aged 35 to 75 years, who underwent unilateral cemented total knee replacement for advanced knee osteoarthritis were included in the study. Patients who had known allergic reactions to tranexamic acid, risk factors of thromboembolism, severe kidney and heart diseases, and blood clotting disorders were excluded. The patients were divided into two groups, A and B. Pre-operatively, patients in Group A were given intraarticular tranexamic acid (3000mg). In Group B, intravenous tranexamic acid (10mg/kg) was given pre-operatively. Outcome parameters studied were drained blood (DB), level of hemoglobin (Hb), blood transfusion (BT), and hematocrit (Hct) after 48 hours of surgery and compared with the preoperative value. Data was entered and analyzed using SPSS version 21.0. Independent sample T-test was applied to compare the hematocrit and hemoglobin difference in the two groups, and the P-value was taken less than 0.05 as significant. Results: Out of the total 36 patients in Group A, there were 20 (55.5%) males and 16 (44.4%) females, while amongst 35 patients in Group B, there were 21 (60%) males and 14 (40%) females. The mean preoperative Haemoglobin (Hb) in Group A was 13.9+1.2 and 13.8+0.9 in Group B (p = 0.44). The mean postoperative Hb in Group A was 12.11±2.47 and 11.24 ± 3.52 in Group B (p = 0.002). The mean variation of Hct in Group A was 4.49 and 6.82 in Group B (p = 0.001). Conclusion: Intra-articular tranexamic acid during total knee joint replacement is a viable alternative to the established intravenous tranexamic acid with statistically significant high postoperative hemoglobin and hematocrit levels.